United States Pharmacopeia Safety Review of Willow Bark - Oketch-Rabah, Hellen A.; Marles, Robin J.; Jordan, Scott A.; Low Dog, Tieraona (Planta Medica, 2019)
Willow bark (Salix spp.) is an ingredient in some dietary supplements. No serious adverse effects were reported from trials of willow bark extracts delivering 120 – 240 mg salicin (the purported active constituent) daily for up to 8 weeks. All studies involved adults only; none involved special subpopulations such as pregnant or breastfeeding women, or children. The most common adverse effects associated with willow bark are gastrointestinal; a few allergic reactions were also reported. Some publications advise caution when taking willow bark. There is a risk of increased bleeding in vulnerable individuals, salicylates cross the placenta and are eliminated slowly in newborns, some persons are sensitive or allergic to aspirin, and children are at risk of Reye syndrome. Concurrent use with other salicylate-containing medicines increases these risks. Metabolism of 240 mg salicin from willow bark could yield 113 mg of salicylic acid, yet dietary supplement products are not required to be labeled with warnings. In contrast, over-the-counter low-dose aspirin (81 mg strength), which delivers 62 mg salicylic acid, is required by law to include cautions, warnings, and contraindications related to its use in pregnant and nursing women, children, and other vulnerable subpopulations, e.g., those using anticoagulants. In the interest of protecting public health, the United States Pharmacopeia has included a cautionary labeling statement in the United States Pharmacopeia Salix Species monograph as follows: “Dosage forms prepared with this article should bear the following statement: ‘Not for use in children, women who are pregnant or nursing, or by persons with known sensitivity to aspirin.’”
Keywords: salix; Salicaceae; willow bark; Reye syndrome; salicin; salicylic acid; salicylates; dietary supplements